The Multitalented MEDIATOR25 - Kazan, Kemal (Frontiers in Plant Science, 2017)
The multi-subunit Mediator complex, which links DNA-bound transcription factors to RNA Pol II during transcription, is an essential regulator of gene expression in all eukaryotes. Individual subunits of the Mediator complex integrate numerous endogenous and exogenous signals. In this paper, diverse regulatory functions performed by MEDIATOR25 (MED25), one of the subunits of the plant Mediator complex are reviewed. MED25 was first identified as a regulator of flowering time and named PHYTOCHROME AND FLOWERING TIME1 (PFT1). Since then, MED25 has been implicated in a range of other plant functions that vary from hormone signalling (JA, ABA, ethylene and IAA) to biotic and abiotic stress tolerance and plant development. MED25 physically interacts with transcriptional activators (e.g. AP2/ERFs, MYCs, and ARFs), repressors (e.g. JAZs and Aux/IAAs), and other Mediator subunits (MED13 and MED16). In addition, various genetic and epigenetic interactions involving MED25 have been reported. These features make MED25 one of the most multifunctional Mediator subunits and provide new insights into the transcriptional control of gene expression in plants.